A Kinetic Study of NH3/H2/CH3OH Fuel Mixture - de Diego Escribano, Irene; Ruiz-Gutiérrez, Adrián; Alzueta Ania, María Uxue (Jornada de Jóvenes Investigadores del I3A, 2025)
This study analyses how the addition of methanol (CH3OH) and hydrogen (H2) affects ammonia (NH3) oxidation, improving its reactivity and reducing the ignition temperature. The impact of stoichiometry and mixture composition on evaluated through species profiles.